Relación entre estrés laboral y resiliencia en trabajadores del sector público y privado - Vasquez Jara, Gisell Milagros (2022)
Work stress is an actual problem in an employees’s lives, so resilience is an important skill that will help mitigate the negative effects of work-related stress and allow the worker to overcome situations that are adverse. The aim of the present study was to identify the relationship between work stress and resilience in employees among the public and private sector. A review was made of papers belonging to the field of Psychology following the PRISMA guidelines (Page et al., 2021) and consulting the databases of ProQuest, APA PsycNET, Google Scholar (Europe 's Journal of Psychology and the Journal of Workplace Behavioral Health) and EBSCO. From this review, 10 complete articles were considered that accomplish the criteria established for this work. A great part of the research showed that the greater the level of developed resilience, the lower the workplace stress will be. The continuation of both variables in further longitudinal studies is important, considering different populations belonging to different countries, in order to detail the relationship between the aforementioned variables inside the organizational field.